Evaluation of the antitumor immune response to C60 fullerene. Issue 2 (13th March 2013) - Didenko, G.; Prylutska, S.; Kichmarenko, Y.; Potebnya, G.; Prylutskyy, Y.; Slobodyanik, N.; Ritter, U.; Scharff, P.
Abstract In vitro experiments have shown that C60 fullerenes exhibit cytotoxic effects against tumor cells and modulate the cytotoxic activity of immune cells. In vivo therapeutic experiments on the model of Lewis lung carcinoma showed that C60 fullerenes exhibit an antimetastatic effect (reduction of metastases by 27%), which is realized by activating macrophages and stimulating the synthesis of humoral factors, which significantly increase the cytotoxicity of treated animals serum.